MAGMATIC ORIGIN OF LOW-CA OLIVINE IN SUBDUCTION-RELATED MAGMAS: CO-EXISTENCE OF CONTRASTING MAGMAS - Kamenetsky V.S.; Elburg M.; Arculus R.; Thomas R. (My University, 2006)
Unravelling the origin of different components contributing to subduction-related magmas is a prerequisite to understanding the sources and processes involved in their origins. Mafic, high-Ca subduction-related magmas from geographically-diverse areas (Indonesia, Solomon Islands, Kamchatka, Valu Fa Ridge) contain two populations of olivine crystals, of which only the high-Ca population (CaO = 0.3-0.5 wt.%) crystallized from the melt that dominantly contributed to the whole rock composition. Forsterite-rich (Fo90-94), low-Ca (CaO < 0.15 wt.%), high-Ni (NiO > 0.3 wt.%) olivine crystals, which constitute 16-37 vol.% of total olivine population, are generally interpreted as mantle or lithospheric xenocrysts. However, in these samples, the olivine shape and chemical zoning, the composition of included minerals (orthopyroxene, clinoenstatite and Cr-spinel) and presence of melt inclusions, are indications that these crystals are phenocrysts from a mafic magma with high silica and low calcium contents. The coexistence of contrasting magmas (mafic high-Ca silica-poor versus low-Ca silica-rich) within a number of arc systems and their mixing may not be a rare event, and should be taken into account when developing models of arc petrogenesis. © 2006 Elsevier B.V. All rights reserved.
Keywords: CLINOENSTATITE; ISLAND-ARC MAGMAS; MAGMATIC INCLUSIONS; MANTLE; OLIVINE; PICRITES; XENOCRYSTS